Testing of Auxotrophic Selection Markers for Use in the Moss Physcomitrella Provides New Insights into the Mechanisms of Targeted Recombination - Ulfstedt, Mikael; Hu, Guo-Zhen; Johansson, Monika; Ronne, Hans (Frontiers in Plant Science, 2017)
The moss Physcomitrella patens is unique among plants in that homologous recombination can be used to knock out genes, just like in yeast. Furthermore, transformed plasmids can be rescued from Physcomitrella back into E. coli, similar to yeast. In the present study, we have tested if a third important tool from yeast molecular genetics, auxotrophic selection markers, can be used in Physcomitrella. Two auxotrophic moss strains were made by knocking out the PpHIS3 geThe moss Physcomitrella patens is unique among plants in that homologous recombination can be used to knock out genes, just like in yeast. Furthermore, transformed plasmids can be rescued from Physcomitrella back into E. coli, similar to yeast. In the present study, we have tested if a third important tool from yeast molecular genetics, auxotrophic selection markers, can be used in Physcomitrella. Two auxotrophic moss strains were made by knocking out the PpHIS3 gene encoding imidazoleglycerol-phosphate dehydratase, and the PpTRP1 gene encoding phosphoribosylanthranilate isomerase, disrupting the biosynthesis of histidine and tryptophan, respectively. The resulting PpHIS3∆ and PpTRP1∆ knockout strains were unable to grow on medium lacking histidine or tryptophan. The PpHIS3∆ strain was used to test selection of transformants by complementation of an auxotrophic marker. We found that the PpHIS3∆ strain could be complemented by transformation with a plasmid expressing the PpHIS3 gene from the CaMV 35S promoter, allowing the strain to grow on medium lacking histidine. Both linearized plasmids and circular supercoiled plasmids could complement the auxotrophic marker, and plasmids from both types of transformants could be rescued back into E. coli. Plasmids rescued from circular transformants were identical to the original plasmid, whereas plasmids rescued from linearized transformants had deletions generated by recombination between micro-homologies in the plasmids. Our results show that cloning by complementation of an auxotrophic marker works in Physcomitrella, which opens the door for using auxotrophic selection markers in moss molecular genetics. This will facilitate the adaptation of shuttle plasmid dependent methods from yeast molecular genetics for use in Physcomitrella.